Future Time Perspective as predictor of self-care behaviors and mental health - Ayala Burboa, Moisés Omar (2025)
This study sought to determine the relationships between Future Time Perspective, Self-Care Behaviors, and Mental Health, and to compare the results based on the adolescents' sex. A total of 181 adolescents participated and answered three questionnaires measuring each of the variables involved. The results of the structural model suggest that Future Time Perspective influences self-care behaviors, which impact mental health. Significant correlations were found between Future Time Perspective and self-care behaviors (r = 0.47, p < 0.001) and mental health problems (r = -.20, p < 0.001), as well as differences based on the adolescents' sex in self-care behaviors (t = 2.09, p < 0.05). The findings of this study contribute to the literature on mental health in adolescents with theoretical and practical implications, establishing an empirical model that links future time perspective with self-care behaviors and mental health, confirming that future time perspective is not only related to mental health, but is a predictor variable that influences health through self-care behaviors, and also reinforces the role of self-care behaviors as a relevant variable for the design of preventive programs aimed at improving adolescent mental health.